Nursing Students' Knowledge Regarding Sexually Transmitted Diseases - Sekeb, Rawaa Talib; Jumaa, Zainalabideen Yasser; Awad , Kadhim Jameel (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Sexually transmitted infections are a severe health issue. Every year, more than 333 million new cases are recorded around the world, with adolescents being the most typically affected demographic. Objectives: To identify the level of nursing students' knowledge regarding sexually transmitted diseases. Methods: A descriptive study design was carried out using an assessment approach from November 12th, 2024, to May 25th, 2025. A non-probability (purposive) sample of 208 nursing students was selected. The questionnaire was designed to identify nursing students' knowledge regarding sexually transmitted diseases in two parts: demographic data (4 items) and nursing students' knowledge regarding sexually transmitted diseases (27 items). Results: The study showed that less than half (48.38%) reported a fair level for the knowledge, less than one third a poor level (27.95%), and less than one quarter a good level (23.65 %).While demonstrating that the overall student knowledge has a significant link with their department, class, at a p-value less than 0.05. Conclusion: The researcher concludes that a significant disparity in students' understanding, highlighting the need for educational development at all levels. Furthermore, statistical analysis revealed a strong correlation between students' general knowledge levels and their department and class (p < 0.05), indicating that academic discipline and year of study play a vital role in knowledge development. Highlights: Less than half of the students had only a fair understanding of STDs. Academic department and class level significantly influenced knowledge. Highlights the urgent need for curriculum-based education interventions. Keywords: Sexually Transmitted Diseases, Nursing Students, Knowledge Level, Descriptive Study, Health Education